Enhancement of running performance following 15 days of hourly exposure to acutely intermittent simulated altitude - Wood, M.; Hopkins, W.; Dowson, M. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
In this novel study of effects of acutely intermittent simulated altitude exposure on running performance, 29 highly trained male soccer and hockey players were each randomly allocated a functional or placebo re-breathing device for 15 d. Each day`s exposure consisted of alternately breathing hypoxic and ambient air for 6 and 4 min respectively over 1 h. Oxygen saturation was monitored individually with pulse oximeters and progressively reduced in the altitude group (Day 1, 90%; Day 15, 77%). Performance tests, which included blood-lactate and heart-rate measurements, were an incremental run to peak speed followed by six maximal-effort sprints; tests were performed 1 d before, 3 d after, and 12 d after the 15-d treatment. Blood-cell counts were taken 1 d pre and post treatment. Measures of blood acid-base status were taken immediately pre and post exposure on Days 1 and 15. Relative to placebo, at 3 d post treatment the altitude group showed a mean increase in peak speed of 2.0% (90% confidence limits, ±0.5%); sprint speed was also relatively faster by 1.5% in the first sprint through 6.9% in the last (±1.9%). Noteworthy changes in blood measures in the altitude group relative to placebo were increases in hemoglobin concentration (1.2%, ±1.9%) and hematocrit (2.0%, ±2.7%) and substantial reductions in exercise lactates and resting and exercise heart rates. Large effects on performance were still present 9 d later. We conclude that acutely intermittent simulated altitude exposure dramatically improves high-intensity running performance possibly via changes in oxygen transport rather than buffering capacity.